Determinants Of Corporate Sustainability Adoption In Firms - Shamil, M.M.M.; Shaikh, Junaid (http://www.internationalconference.com.my/proceeding.html, 2012)
Sustainable development has become a priority of governments and intergovernmental organizations such as United Nations in the 21st century. In this context how businesses integrate and implement sustainable development is of importance as a key player in any economy. Further literature is emerging on corporate sustainability as a multidimensional construct to explain the application of sustainable development at micro level. This paper proposes a theoretical framework to explicate the influence of external and internal determinants on corporate sustainability adoption in firms. The framework proposes institutional pressure and stakeholder pressure as external determinant, dominant motivating principle as the internal determinant and integration capability as the moderator of the link between external determinants and corporate sustainability adoption. Thus, the theoretical framework provides the opportunity to test the model in different contexts extends institutional theory and stakeholder theory to explain corporate sustainability adoption, introduces a limitedly used determinant dominant motivating principle in research. Further, the framework draws integration capability as a moderator from resource based theory and dynamic capability theory. Based on the theoretical framework the authors propose five propositions in the form of a causal model that links the constructs together. The proposed theoretical framework should stimulate further discussion on corporate sustainability and extend to incorporate determinants from other organizational theories.